2013
DOI: 10.2478/jee-2013-0047
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic Contacts to P–GaN Based on the Single–Walled Carbon Nanotubes

Abstract: We have designed and verified a new structure for ohmic contacts to p-GaN, mainly for applications in light emitting devices based on a layer of single-walled carbon nanotubes (SWCNT) and metallic layers of Cr and Au, namely in configuration Au/Cr/SWCNT/p-GaN. The layer of carbon nanotubes was deposited on p-GaN by spraying a solution of synthesized SWCNTs, while the layers of Cr and Au were vapour deposited. The effects of the annealing temperature and time upon the electrical properties of Au/Cr/SWCNT/p-GaN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Recently, Liday et al have reported that a combination of SWCNTs and reduced graphene oxide (rGO) as an interlayer allows the metallization to form an ohmic contact on a p-GaN layer. 22) Considering the relatively low transmittance and high sheet resistance of rGO compared with those of CVD graphene, the application of such combinations as a transparent electrode requires more breakthroughs. 23) Different from the above study, which considers the p-type semiconducting property of the SWCNTs in forming an ohmic contact, here, we report on the integration of CVD graphene with SWCNTs in an attempt to produce a reliable hybrid electrode with tunable properties.…”
mentioning
confidence: 99%
“…Recently, Liday et al have reported that a combination of SWCNTs and reduced graphene oxide (rGO) as an interlayer allows the metallization to form an ohmic contact on a p-GaN layer. 22) Considering the relatively low transmittance and high sheet resistance of rGO compared with those of CVD graphene, the application of such combinations as a transparent electrode requires more breakthroughs. 23) Different from the above study, which considers the p-type semiconducting property of the SWCNTs in forming an ohmic contact, here, we report on the integration of CVD graphene with SWCNTs in an attempt to produce a reliable hybrid electrode with tunable properties.…”
mentioning
confidence: 99%
“…Due to their one dimensional structure CNTs exhibit field emission properties. The first applications of CNTs for ohmic contacts to p-GaN showed that the contact resistivity was lower than in the case of an Au/Ni contact [1,2].…”
Section: Introductionmentioning
confidence: 99%